Transcriptome Analysis of Salicylic Acid Treatment in Rehmannia glutinosa Hairy Roots Using RNA-seq Technique for Identification of Genes Involved in Acteoside Biosynthesis - Wang, Fengqing; Zhi, Jingyu; Zhang, Zhongyi; Wang, Lina; Suo, Yanfei; Xie, Caixia; Li, Mingjie; Zhang, Bao; Du, Jiafang; Gu, Li; Sun, Hongzheng (Frontiers in Plant Science, 2017)
Rehmannia glutinosa is a common bulk medicinal material that has been widely used in China due to its active ingredients. Acteoside, one of the ingredients, has antioxidant, antinephritic, anti-inﬂammatory, hepatoprotective, immunomodulatory and neuroprotective effects, is usually selected as a quality-control component for R. glutinosa herb in the Chinese Pharmacopoeia. The acteoside biosynthesis pathway in R. glutinosa has not yet been clearly established. Herein, we describe the establishment of a genetic transformation system for R. glutinosa mediated by Agrobacterium rhizogenes. We screened the optimal elicitors that markedly increased acteoside accumulation in R. glutinosa hairy roots. We found that acteoside accumulation dramatically increased with the addition of salicylic acid (SA); the optimal SA dose was 25 μmol/L for hairy roots. RNA-seq was applied to analyze the transcriptomic changes in hairy roots treated with SA for 24 h in comparison with an untreated control. A total of 3,716, 4,018 and 2,715 differentially expressed transcripts (DETs) were identified in 0 h-vs-12 h, 0 h-vs-24 h and 12 h-vs-24 h libraries, respectively. KEGG pathway-based analysis revealed that 127 DETs were enriched in “phenylpropanoid biosynthesis.” Of 219 putative unigenes involved in acteoside biosynthesis, 54 were found to be up-regulated at at least one of the time points after SA treatment. Selected candidate genes were analyzed by quantitative real-time PCR (qRT-PCR) in hairy roots with SA, methyl jasmonate (MeJA), AgNO3 (Ag+) and putrescine (Put) treatment. All genes investigated were up-regulated by SA treatment, and most candidate genes were weakly increased by MeJA to some degree. Furthermore, transcription abundance of eight candidate genes in tuberous roots of the high-acteoside-content (HA) cultivar QH were higher than those of the low-acteoside-content (LA) cultivar Wen 85-5. These results will pave the way for understanding the molecular basis of acteoside biosynthesis in R. glutinosa, and can serve as a basis for future validation studies.